Rancang Bangun Alat Laminar Air Flow Cabinet dan Pendampingannya di UKM Thani Jamur Magetan - Tukiran, Tukiran (Universitas Negeri Surabaya, 2024)
A survey conducted at Thani Oyster Mushroom UKM in Magetan, followed by interviews with the owners, revealed that the main challenges faced by UKM were frequent failures and difficulties in finding trusted partners who were able to prepare oyster mushroom seeds well. This is mainly caused by less than sterile room conditions and inadequate facilities. Typically, mushroom breeding consists of the following stages: The process involves four steps: 1) cultivating an uncontaminated culture, 2) creating a starter culture, 3) producing a primary seed culture, and 4) producing final production seeds. Partners often encounter challenges and setbacks when trying to cultivate this mushroom. Creating culture media is a crucial step in the process of preparing pure culture. To date, partners have utilized PDA as a specialized medium for cultivating single strains of microorganisms, and this has been achieved using less sterile equipment and facilities. As a result, the media will be contaminated by pest bacteria, weeds, and other elements that are difficult to avoid, resulting in low success rates and frequent failures. The alternative proposed in this PKM activity is the need to build an aseptic isolation room or enclosure, which is specifically known as a Laminar Air Flow Cabinet (LAFC). The instrument is equipped with a continuously operating ultraviolet light, TL lamp, blower and air filter to ensure a sterile working environment by removing dust, dirt, spores and other particles that inhibit the germination of fungal seeds. Initial support provided to partners in utilizing LAFC resulted in a success rate of approximately 77% (10 out of 13 petri bottles) in mushroom mycelium cultivation.